Black Beauty: An Animal Classic - Francis, Pauline (Evans Brothers Ltd, 2001)
This book tells the story of a working horse in Victorian England. Black Beauty has to adapt to life with a series of different masters and grooms, some of them kindly but many of them cruel or thoughtless. He survives flood, fire and fever until he feels ready to die, but then he is taken to yet another horse sale...
Keywords: Animal Stories